STUDENTS’ EXPERIENCES IN FOLLOWING TEACHING AND LEARNING PROCESS OF MICROTEACHING CLASSES AT ENGLISH EDUCATION STUDY PROGRAM OF MUHAMMADIYAH UNIVERSITY OF BENGKULU - Lisa Rusmeini; Kiagus Baluqiah (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The purpose of this research was to determine students’ experiences in following teaching and learning process of microteaching classes at English Education Program Muhammadiyah University of Bengkulu. This research designed using qualitative research that uses descriptive methods as a procedure to obtain descriptive data. The researcher taken sixth semester students to collect research data. The instrument of this research used questionnaire to get the data about students’ experiences in following teaching and learning process of microteaching classes, in the form of open-ended questions with a choice of Yes or No. In addition, there are 16 question items given to the sixth semester students based on the adoption of the Microteaching Book (Sofendi, 2014). And video observations are used to ensure the student answers so that the data is more valid. The results showed that the students gained overall experience in following teaching and learning process of the microteaching class at English Education Program of Muhammadiyah University of Bengkulu. Keywords: Experience, Teaching and Learning, Microteaching Class